STUDENTS’ VIEWS ON THE UTILIZATION OF KINEMASTER APPLICATIONS FOR PICTURE DESCRIBING TECHNIQUE IN ENGLISH FOR TOURISM SUBJECT - Fuad Abdul Baqi (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The purpose of this research was to determine students' views on the Utilization of KineMaster Applications in Implementing Picture Describing Technique of English for Tourism. The method used is the descriptive verification method with ex post facto and survey approaches. The instrument used was a questionnaire distributed to students of English Department of STKIP La Tansa Mahiro. The results showed in general, it was found that the most of respondents agree that Picture Describing Technique using KineMaster application is very beneficial and relevant to be used in English for Tourism class. This is evidenced by the results of 75% of students agree that Picture Describing Technique using KineMaster application is quite relevant and appropriate to be implemented in English for Tourism, 20% strongly agree and 4,2% disagree